(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Human resources or HR is an integral part of any company. A good HR department will keep the company running smoothly, successfully hiring appropriately qualified staff and letting others go legally, help deal with employee grievances, meet legal employment requirements, use best practice employment guidelines and much more. A well-run and managed HR department can increase morale, reduce employee turnover and help a business run smoothly and in many cases remain competitive. Employees should be seen as the most valued asset of a company and treated accordingly. Because of this, to make sure an HR department is operating to its best capacity, it is important to run a periodic HR audit. Similar to a financial audit, an HR audit is a way to diagnose problems in a company’s HR department. An HR audit can be done through self-assessment, internally, or can be done by hiring a professional audit company, to undertake an audit. An HR audit and the subsequent HR audit report will pinpoint where there are weaknesses or risks in the HR department and help address these. In this paper we find out need and advantages of HR Audit.